2022
DOI: 10.1101/2022.09.15.508205
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Electrochemical disruption of extracellular electron transfer inhibits Pseudomonas aeruginosa cell survival within biofilms and is synergistic with antibiotic treatment

Abstract: Survival of cells within oxygen-limited regions in Pseudomonas aeruginosa biofilms is enabled by using small redox active molecules as electron shuttles to access distal oxidants. This respiratory versatility makes P. aeruginosa biofilms common in chronic wound infections and recalcitrant to treatment. Here, we show that electrochemically controlling the redox state of these electron shuttles, specifically pyocyanin, can impact cell survival within anaerobic P. aeruginosa biofilms and can act synergistically w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Pyocyanin is a redox active small molecule secreted by P. aeruginosa to act as an electron shuttle supporting aerobic respiration under the microaerobic conditions in a biofilm (22)(23). NahK is not alone as a regulator of PQS in the GacS MKN; it has also been reported that ∆rsmA, ∆gacS and ∆retS overproduce pyocyanin and ∆rsmY and ∆rsmZ underproduce pyocyanin, relative to wild-type (19,24).…”
mentioning
confidence: 99%
“…Pyocyanin is a redox active small molecule secreted by P. aeruginosa to act as an electron shuttle supporting aerobic respiration under the microaerobic conditions in a biofilm (22)(23). NahK is not alone as a regulator of PQS in the GacS MKN; it has also been reported that ∆rsmA, ∆gacS and ∆retS overproduce pyocyanin and ∆rsmY and ∆rsmZ underproduce pyocyanin, relative to wild-type (19,24).…”
mentioning
confidence: 99%